2019
DOI: 10.1073/pnas.1808307116
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in school-based disciplinary actions are associated with county-level rates of racial bias

Abstract: There are substantial gaps in educational outcomes between black and white students in the United States. Recently, increased attention has focused on differences in the rates at which black and white students are disciplined, finding that black students are more likely to be seen as problematic and more likely to be punished than white students are for the same offense. Although these disparities suggest that racial biases are a contributor, no previous research has shown associations with psychological measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
138
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(146 citation statements)
references
References 31 publications
(32 reference statements)
7
138
1
Order By: Relevance
“…Thus, we ran separate analyses for Explicit Racial Attitudes and Implicit Racial Attitudes. This approach is also consistent with Riddle and Sinclair [28].…”
Section: Empirical Analysissupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, we ran separate analyses for Explicit Racial Attitudes and Implicit Racial Attitudes. This approach is also consistent with Riddle and Sinclair [28].…”
Section: Empirical Analysissupporting
confidence: 87%
“…However, for many of the reasons articulated by Payne et al [19,20]., bias captured at the community-level is likely to offer better explanatory power (see also [23]). Consistent with this position, community-level racial attitudes are linked with racial differences in infant health outcomes [24], Black individuals' death rates due to cardiovascular disease [25], and mortality risk [26], as well as other important community outcomes, such as lethal force in policing [27], punishment of Black school children [28], and reactions to social justice movements [29], among others.…”
Section: Theoretical Frameworkmentioning
confidence: 89%
“…Furthermore, as hypothesized by CRT, research has also found that the racial/ethnic disparities in schools cannot be explained by differences in individual-level factorssuch as differential rates of misbehavior by students across races/ethnicities (Owens & Mclanahan, 2019;Skiba et al 2015). Rather, differential treatment (Owens & Mclanahan, 2019), across-and within-school differences (Gopalan & Nelson, 2019) as well as implicit racial biases (Riddle & Sinclair, 2019) at the county-level are significantly associated with racial/ethnic discipline gaps. In other words, this study calls for a closer look at such contextual factors using national data.…”
Section: Theoretical/conceptual Frameworkmentioning
confidence: 93%
“…For instance, this approach has revealed that in regions where White people are more implicitly biased against Black people, more Black people are killed by police (Hehman, Flake, & Calanchini, 2018). Other research adopting a regional approach has found links between regional intergroup biases and health (Leitner, Hehman, Ayduk, & Mendoza-Denton, 2016a, 2016bOrchard & Price, 2017), segregation (Rae, Newheiser, & Olson, 2015), ethnic diversity (Sadler & Devos, 2018), education (Riddle & Sinclair, 2019), and federal policy (Leitner, Hehman, & Snowden, 2018;Ofosu, Chambers, Chen, & Hehman, 2019).…”
Section: Using Environmental Features To Maximize Prediction Of Regiomentioning
confidence: 99%
“…racially segregated housing, the number of Black individuals killed by police, disparities in education-related outcomes, and disparities in income. 2 Previous work has linked these outcomes with White-Black racial bias (Dovidio & Gaertner, 2000;Hehman et al, 2018;Rae et al, 2015;Riddle & Sinclair, 2019). Segregation was represented by the isolation index as calculated by Logan and Stults (2011), and disproportionate deaths from police as calculated by Hehman and colleagues (2018).…”
Section: Examining the Predictive Validity Of Environmental Featuresmentioning
confidence: 99%